A new strategy to synthesize anisotropic SmCo5 nanomagnets. Issue 18 (30th April 2018) - Shen, Bo; Yu, Chao; Su, Dong; Yin, Zhouyang; Li, Junrui; Xi, Zheng; Sun, Shouheng
Abstract : Anisotropic SmCo5 nanoplates with a large coercivity of 30.1 kOe were synthesized by the reduction of Sm(OH)3 –Co nanocomposites. Abstract : We report a simple strategy to synthesize anisotropic SmCo5 nanoplates. The strategy involves the pre-synthesis of 125 × 12 nm Sm(OH)3 nanorods and 10 nm Co nanoparticles followed by the self-assembly of these nanorods and nanoparticles into Sm(OH)3 –Co nanocomposites. Once embedded in a CaO matrix, the nanocomposite is subjected to high temperature (850 °C) annealing in the presence of Ca, leading to the formation of 125 × 10 nm SmCo5 nanoplates, which are dispersible in ethanol, allowing the alignment in epoxy resin under a 20 kOe magnetic field. The aligned SmCo5 nanoplates show a square hysteresis behavior with room temperature coercivity reaching 30.1 kOe, which is among the highest values ever reported for SmCo5 made from chemical methods. This work provides a new approach to high-performance anisotropic SmCo5 for permanent magnetic applications.